Correlação dos níveis plasmáticos de proproteína convertase subtilisina kexina tipo 9 (PCSK9) com parâmetros do perfil lipídico e do estresse oxidativo em mulheres jovens e na pós-menopausa - Aline da Paz Fernandes (2018)
The hormone use, combined oral contraceptives (COC) and postmenopausal hormone therapy (MHT), as well as aging have a direct effect on lipid metabolism and may trigger cardiovascular changes. Pro-protein convertase subtilisin kexina type 9 (PCSK9) is a new component of lipid metabolism associated with the development of dyslipidemia, atherosclerosis and cardiovascular events. The aim of this study was to investigate the correlation use between COC and MHT in the lipid profile parameters towards PSCK9 and oxidative stress markers in young and postmenopausal women. The study included 79 women distributed into four groups: young women using COC (COC, n=20) or not (no-COC, n=20), and postmenopausal women performing MHT (THM, n=17) or not (no-THM, n =22). Lipid profile parameters were determined by colorimetric-enzymatic methodologies. PCSK9 plasma levels were quantified by ELISA. MTT and TBARS levels were used to evaluate oxidative stress. Statistical analyzes were performed by MINITAB program version 17.0. Significant differences were observed in relation to total cholesterol (TC) and tryglicerides (TG) when comparing no-COC and COC, and no-COC and no-THM groups; in relation to high-density lipoprotein cholesterol (LDLc) when comparing no-COC and no-THM, and no-THM and THM groups. The young people group who used hormone had higher PCSK9 plasma levels than young group who did not use (p <0.05). The highest TBARS level was verified in COC group in relation no-COC groups. PCSK9 plasma levels correlated positively with lipid profile parameter TC, suggesting that PCSK9 increase may have some effect on dyslipidemia. PCSK9 also correlated with MTT variable in COC group. By considering the data of lipid profile parameters, PCSK9 and oxidative stress markers, these were found to be are higher in young women who use COC; whereas in the group of postmenopausal women in THM, better results were found for the lipid profile compared to those who did not take. Our results suggest that the hormone use, age-related, may interfere with lipid metabolism by different mechanisms.